ICE manual of bridge engineering - Parke, G. A. R.; Hewson, Nigel R. (ICE manuals, 2022)
Now in its third edition, the 'ICE Manual of Bridge Engineering' is the authoritative guide to core knowledge on all aspects on bridge engineering. The book has been written by a team of leading experts and contains all of the key topics that any bridge engineer will need to refer to bridge design, materials and management of bridges and loadings and bearings amongst many others.